The risk of repeated self-harm and suicide after emergency department presentation with self-harm in mental health presenters: a retrospective cohort study with data linkage in Queensland, AustraliaResearch in context - Richard A.F. Pellatt; David R. Painter; Jesse T. Young; Kairi Kõlves; Gerben Keijzers; Stuart A. Kinner; Ed Heffernan; Julia Crilly; Marc Broadbent; Amy Johnston; Melinda Martin-Khan; Paul Scuffham; et al. (The Lancet Regional Health. Western Pacific, 2025)
Summary: Background: Presentation to the emergency department (ED) with an index episode of self-harm is recognised as a risk factor for subsequent repeated self-harm and suicide. We describe demographic and clinical characteristics of adults (>18 years) presenting with mental health problems and self-harm to EDs in Queensland, Australia, and identify risk factors associated with repeated self-harm and suicide. Methods: This was a state-wide retrospective cohort study of adults presenting with an index self-harm presentation to any of the 27 public EDs in Queensland, Australia, over six years (1st January 2012 to 31st December 2017). We linked ED records with a state-wide death register. Primary outcomes were re-presentation with self-harm, or death by suicide. We constructed a multivariable Cox regression model to identify independent risk factors for re-presentation with self-harm, or death by suicide. We calculated the risk of repeated ED presentation for self-harm and suicide at 12- and 24-months. Findings: During the study period, 43,797 individuals presented to Queensland EDs with a self-harm related diagnosis. Half of the cohort were female (n = 20,980, 47.9%) and under age 35 (n = 23,871, 54.5%). A quarter (n = 10,991; 25.1%) had a repeated episode of self-harm and 515 (1.2%) died by suicide. Socioeconomic disadvantage, arrival by ambulance, self-presentation, small/medium hospital size, less-urgent triage category, not admitted status and previous mental health or physical health visits were associated with a re-presentation with self-harm. Suicide was associated with male sex, older age, and hospital admission. The repeated self-harm risk was 18.9% (95%CI, 18.5%–19.3%) at 12-months and 24.3% (95%CI, 23.9%–24.7%) at 24-months. The suicide risk was 0.7% (95%CI, 0.6%–0.7%) at 12-months and 1.0% (95%CI, 0.9%–1.1%) at 24-months. Interpretation: One in four people re-presented to ED with self-harm. Suicide was particularly associated with older males. Implementing evidence-based interventions to support people presenting to ED with self-harm should be a public health priority. Funding: This study was funded by an Emergency Medicine Foundation (EMF) grant (EMJS-382-R35-2021) and a National Health and Research Council Grant (1121898).